PERAN PENDIDIKAN DALAM MEMBENTUK SIKAP TOLERANSI DAN KERJA SAMA DI SEKOLAH DASAR - Widiastuti, Widiastuti; Ariani, Risda; Saputri, Tia (Universitas Sulawesi Tenggara, 2023)
Character education has a strategic role in forming attitudes of tolerance and cooperation in elementary schools. This study aims to examine how education through the curriculum, the role of teachers, and the school environment can encourage the formation of values of tolerance and cooperation in students. The method used is a combination of qualitative and quantitative research with data collection techniques in the form of observation, interviews, questionnaires, and documentation studies. The results of the study indicate that students have a good level of tolerance and cooperation, supported by a curriculum that integrates the values of diversity and togetherness. Teachers play an important role as facilitators and role models, using collaborative learning strategies to develop students' social skills. The school environment also makes a positive contribution through character education programs that create a culture of tolerance and cooperation. However, obstacles such as limited facilities, minimal teacher training, and low parental involvement are still challenges that need to be overcome. This study concludes that synergy between the curriculum, teachers, and the school environment is very important to produce a young generation who are not only academically superior but also have a tolerant and cooperative character.